Mengupas Politik Lewat Animasi Pak Tani & Mawar Kecil, serta Rahasia di Baliknya - Mahriyuni, Mahriyuni; Tausya, Resi Syahrani; Hasibuan, Alika Sandra; T.Syarfina, T.Syarfina; Pramuniati, Isda (ppjbsip, 2024)
This research aims to describe the meaning of connotation, denotation, and political myth through the animation